Interaction between novel oscillation within the ventromedial hypothalamus and the sympathetic nervous system. (20th February 2017) - Iigaya, Kamon; Okazaki, Shuntaro; Minoura, Yoshino; Onimaru, Hiroshi
Highlights: The ventromedial hypothalamus (VMH) is involved in various vital functions. We found a novel oscillation (<0.1 Hz) in the VMH of the slice preparations. This VMH oscillation responded to changes in glucose concentration. A predominant positive-correlation was present between the VMH and sympathetic nerve activity. This neuronal burst activity may be linked to central sympathetic nerve activity. Abstract: The ventromedial hypothalamus (VMH) is known to play an important role in feeding behavior and the control of sympathetic nerve activity (SNA). We report the identification of novel neuron groups that showed oscillations on both sides of the VMH in hypothalamus slice preparations from juvenile rats of postnatal days 5–14. We detected spontaneous rhythmic burst activity with a frequency of around 0.06 Hz typically in the dorsolateral region of the VMH (i.e., VMH oscillation) using optical recordings (voltage and calcium imaging), field potential recordings and intracellular membrane potential recordings. The oscillation was also confirmed after isolation of the VMH from other hypothalamic structures. The frequency of oscillation was increased by lowering the glucose concentration of the superfusate. To evaluate the relation between VMH oscillation and SNA, we simultaneously recorded VMH oscillation, SNA from the thoracic sympathetic nerve trunk and phrenic nerve discharge (Phr) in the decerebrate and arterially perfused in situ preparation from juvenile rats of postnatal days 5–11. Power spectral analysis in the arterially perfused in situ rat preparation revealed similar peak values to those of slice preparations within the low-frequency range between the VMH oscillation and sympathetic nerve trunk activity. In addition, we analyzed cross-correlations between the VMH, SNA and Phr. The results revealed that a predominant positive correlation of the VMH activity with the SNA existed with an average time lag of 2.4 s, suggesting the presence of functional couplings between the VMH and SNA (and respiratory center) in the lower brainstem and spinal cord. We hypothesize that the VMH oscillation might be involved in low-frequency modulation of the SNA.